2012
DOI: 10.1080/1539445x.2010.532848
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Emulsion-Templated Acrylic-Based Porous Polymers: From Brittle to Elastomeric

Abstract: High internal phase emulsion polymers (PolyHIPEs) are novel materials that have high porosityand interconnected open-cell structure and are used in various applications such as supports for catalytic systems, media for separation of similar molecules, and scaffolds for tissue engineering. In this study, 90% porous acrylic based polyHIPE structures with various cellular structure and mechanical characteristics were developed by using stearyl acrylate (SA), isodecyl acrylate (IDA), isobornyl methacrylate (IBMA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Crosslinkers are the precursors with at least two reactive ends to connect primary polymer chains by forming intermolecular linkages ( Figure 9A). Using an external crosslinking agent increases the degree of crosslinking of the polymer phase, and it improves the stiffness of the materials (Tunc et al, 2012). The most known crosslinker is DVB, used in the composition of styrene HIPEs (Akay et al, 2004;Sevšek et al, 2014;Woodward et al, 2017; Figures 9B,C).…”
Section: Crosslinker (Crosslinking Agent)mentioning
confidence: 99%
See 1 more Smart Citation
“…Crosslinkers are the precursors with at least two reactive ends to connect primary polymer chains by forming intermolecular linkages ( Figure 9A). Using an external crosslinking agent increases the degree of crosslinking of the polymer phase, and it improves the stiffness of the materials (Tunc et al, 2012). The most known crosslinker is DVB, used in the composition of styrene HIPEs (Akay et al, 2004;Sevšek et al, 2014;Woodward et al, 2017; Figures 9B,C).…”
Section: Crosslinker (Crosslinking Agent)mentioning
confidence: 99%
“…Ammonium persulphate (APS) ( Moglia et al, 2011 ) and potassium persulphate (KPS) ( Lumelsky et al, 2008 , 2009 ; Tunc et al, 2012 ) are water-soluble oxidising agents that are used as redox initiators in radical crosslinking of the macromer chains. They have been reported to be introduced into the water phase of the styrene ( Bokhari et al, 2005 ; Audouin et al, 2012 ), dextran, ( Zhou et al, 2012a ) or polypropylene fumarate (PPF) ( Christenson et al, 2007 ; Moglia et al, 2011 ) HIPEs with the concentration of 1–5% w/v of the aqueous phase.…”
Section: Development Of the Emulsion Templated Scaffoldsmentioning
confidence: 99%
“…20 The emulsions consist of an external continuous monomer phase and an internal droplet phase with volume fraction of at least 0.74. 21,22 This HIPE templating method is exible and easy to control pore structure and size as well as porosity by varying the compositions of the emulsions, compared with other methods for the fabrication of porous polymers. [23][24][25] In previous reports, polyHIPEs are fabricated by various monomer precursors, such as styrene, 26,27 4-vinylbenzyl chloride, 28 methyl methacrylate, 27,29 2-hydroxyethyl methacrylate, 30 2-ethylhexyl acrylate, 31 stearyl methacrylate, 32 hexauorobutyl acrylate, 33 butyl acrylate, 34 and so on, giving mechanical properties that range from elastomeric to extremely tough and rigid.…”
Section: Introductionmentioning
confidence: 99%
“…Pulko et al [36] prepared bendable poly-HIPE membranes based on glycidyl methacrylate, ethyleneglycol dimethacrylate and ethylhexyl methacrylate. Recently, Tunc et al [37] reported that polyHIPEs can be tailored from rigid materials to elastomers by tuning the template composition, i.e. varying the acrylate/divinylbenzene ratio within emulsion template.…”
Section: Introductionmentioning
confidence: 99%